Therapeutic Role of Hematopoietic Stem Cells in Autism Spectrum Disorder-Related Inflammation - Siniscalco, Dario; Bradstreet, James J.; Antonucci, Nicola (Frontiers in Immunology, 2013)
Autism and autism spectrum disorders (ASDs) are heterogeneous, severe neurodevelopmental disorders with core symptoms of dysfunctions in social interactions and communication skills, restricted interests, repetitive - stereotypic verbal and non-verbal behaviours. Biomolecular evidence points to complex gene-environmental interactions in ASDs. Several biochemical processes are associated with ASDs: oxidative stress (including endoplasmic reticulum stress), decreased methylation capacity, limited production of glutathione; mitochondrial dysfunction, intestinal dysbiosis, increased toxic metal burden and various immune abnormalities. The known immunological disorders include: T-lymphocyte populations and function, gene expression changes in monocytes, several autoimmune-related findings, high levels of N-acetylgalactosaminidase (which precludes macrophage activation), and primary immune deficiencies. These immunological observations may result in minicolumn structural changes in the brain, as well as, abnormal immune mediation of synaptic functions. Equally, these immune dysregulations serve as the rationale for immune-directed interventions such as hematopoietic stem cells (HSCs), which are pivotal in controlling chronic inflammation and in the restoration of immunological balance. These properties make them intriguing potential agents for ASD treatments. This prospective review will focus on the current state-of-the-art knowledge and challenges intrinsic in the application of hematopoietic stem cells for ASD-related immunological disorders.